2017
DOI: 10.1016/j.jtho.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Mesothelioma Diagnosis in China

Abstract: Background In the Western World malignant mesothelioma (MM) is most prevalent in the pleura of older males professionally exposed to asbestos. Information about MM from rapidly industrializing countries, such as China, is minimal. There is concern that a proportion of MM diagnoses in China may be incorrect because most Chinese physicians do not have experience diagnosing this rare cancer. We recently reported an unusual high incidence of peritoneal MM among Eastern Chinese female patients. Here, we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
1
37
0
2
Order By: Relevance
“…This may suggest that VATS have superior sensitivity to pleuroscopy in ruling out malignancy in pleural effusions of unknown origin (7,14). However, inter-center differences in experience of thoracoscopists and/or pathologists might also be of importance (15). No prospective studies so far have compared the sensitivity of pleuroscopy and VATS.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that VATS have superior sensitivity to pleuroscopy in ruling out malignancy in pleural effusions of unknown origin (7,14). However, inter-center differences in experience of thoracoscopists and/or pathologists might also be of importance (15). No prospective studies so far have compared the sensitivity of pleuroscopy and VATS.…”
Section: Discussionmentioning
confidence: 99%
“…The most specific marker for mesothelioma is WT1. However, for peritoneal mesotheliomas in women, WT1 is not helpful as it stains ovarian cancers; instead ER and PR staining should be used (4,5).…”
Section: Pathologymentioning
confidence: 99%
“…As we were reviewing the accuracy of the diagnoses of mesothelioma in Eastern China (5,52) in mesotheliomas linked to inherited germline BAP1 mutations, to environmental exposure occurring since birth, radiation or to other yet unknown carcinogens (13,39). In the absence of occupational asbestos exposure, the expected M:F ratio is close to 1:1 (12).…”
Section: Unexplained Findings and Opportunities For Researchmentioning
confidence: 99%
“…In France, the accuracy of initial diagnosis of MM was reported only in 67% of cases (23). We recently reviewed 92 pathological diagnoses of MM from China and found that the diagnostic accuracy rate was about 56.6% (24). In our experience, there are about 1/10 cases of MMs misdiagnosed in the US.…”
Section: Review Articlementioning
confidence: 77%